Innovation of Audio Visual Teaching Materials Based on Animated Videos as Edupreneur Development at SDN Karangrejo II Purwosari - Ikhlasud Dafa; M. Khusni Mubarak (Islamic Journal of Teaching and Learning, 2026)
Background: The rapid development of educational technology demands innovative audio-visual teaching materials that not only support learning processes but also foster edupreneurship from an early age. In elementary schools, the limited use of creative digital media often hinders the development of students' creativity and entrepreneurial awareness. Objective: This study aims to develop animated video-based audio-visual teaching materials as a form of learning innovation and edupreneurship development at SDN Karangrejo II Purwosari. Method: The research employed a Research and Development (R&D) method using a systematic development model consisting of needs analysis, product design, development, validation, and limited trials. The research subjects included teachers and elementary school students at SDN Karangrejo II Purwosari. Findings and Implications: The main product of this study is an animated video-based audio-visual teaching material designed to be educational, engaging, and economically valuable. The results show that the developed product is feasible for use, as indicated by expert validation results in terms of content, media, and instructional design, as well as positive responses from users. Conclusion: The developed teaching material contributes to learning innovation and supports educational development by integrating creativity, technology, and educational value in elementary education.